No maternal effects after stimulation of the melanization response in the yellow fever mosquito Aedes aegypti - Voordouw, Maarten; Lambrechts, Louis; Koella, Jacob (My University, 2008)
The costs and benefits of activating the immune system can reach across generations. Thus, in vertebrates and in several invertebrates, stimulating the immune system of a female can enhance immunity of her offspring or decrease offspring fitness. We evaluated the potential maternally transmitted costs and benefits of the melanization response, an innate immune response of insects that helps to protect mosquitoes from malaria parasites. We manipulated the maternal melanization response of the yellow fever mosquito Aedes aegypti by inoculating female mosquitoes with negatively charged sephadex beads or with immunologically inert glass beads; a control group was not inoculated. In the next generation, we assayed the melanization response and measured three other life-history traits: survival up to emergence, the age at emergence, and body size (estimated as wing length). We found no evidence of fitness costs or benefits for the offspring. A retrospective power analysis found that our experiment would have detected an effect size that is three times smaller than the maternal immune priming effects that have been reported in the literature. We did find a strong correlation between offspring wing length and melanization response. Overall, our findings indicate that trans-generational immune priming in invertebrates cannot be generalized, and that it may depend on the species, the immune challenge, and the environmental conditions.